Antibacterial and antibiofilm activity of mint leaves (Mentha piperita L) extracts against Streptococcus mutans UA159: a laboratory experiment - Muhtar, Azmi Nur Azizah; Atthoriq, Adriansyah Altaf; Jeffrey, Jeffrey; Djohan, Frita Ferlita Shafri; Soerachman, Badi (Universitas Padjadjaran, 2024)
Introduction: Oral health is a major concern in healthcare worldwide, with dental caries being a prevalent issue among children and adults. Streptococcus mutans is a primary bacterium implicated in the development of dental caries due to its acidogenic nature. Mint leaf (Mentha piperita L.) is a unique herbal plant that has antibacterial and antibiofilm properties against S. mutans and minimal side effects. The purpose of this study was to analyze the antibacterial effectiveness of mint leaf against the growth of S. mutans UA159 and its antibiofilm effects. Methods: This study was conducted experimentally with the posttest-only control group design, using the broth microdilution method in 6 test groups, namely mint leaf extract with a concentration of 3.125, 6.25, 12.5, 25, 50, and 100% and also two control groups, namely the negative control using aquadest and the positive control using 0.2% chlorhexidine. Biofilm growth is determined by comparing Optical Density (OD) values and then calculating the percentage of eradication of S. mutans biofilm formation. Results: The results indicated that the mint leaf extract exhibited antibacterial effects against S. mutans, with the largest inhibition zone diameter observed at a 100% concentration. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC)90 values using the broth microdilution method in this study were 12.5% and 100% concentrations, respectively. Mint leaf extract has been shown to significantly inhibit the growth of S. mutans (p<0.05). The results of the inhibition test on biofilm formation at a concentration of 100% averaged 87.39%. Conclusion: Mint leaf extract has an antibacterial and antibiofilm effect on the growth of S. mutans. The level of inhibition of mint leaf extract on the growth of S. mutans is proportional to its concentration; the higher the concentration of the extract, the stronger the inhibitory ability.KeywordAnti-Bacterial agents, biofilms, Mentha piperita, oral health, Streptococcus mutans.